Vasovagal reaction among blood donors in Hospital Universiti Sains Malaysia - Ibrahim, Nur Nasuha (2023)
Introduction: The blood donor return rate is mostly affected by adverse events (AE), particularly vasovagal reactions (VVR). VVR are caused by the parasympathetic nervous system being stimulated during blood donation process. Objectives: This study aims to determine the prevalence of VVR among blood donors and to study its associated biological factors at Hospital Universiti Sains Malaysia (USM). Methodology: The first part of this study is a cross-sectional study that included all blood donors who attended the Transfusion Medicine Unit (TMU) of Hospital USM from June 2018 until June 2021. The donors who developed VVR within this time frame were identified. The information was obtained from the transfusion medicine information system (My Transfusi) and the donor's adverse reaction form. The second part is a case-control study that analyses the association of sociodemographic and donation details among blood donors using logistic regression. The case group includes a blood donor who developed a vasovagal reaction. The control group was chosen from blood donors who did not develop vasovagal reactions in a 1:2 ratio randomly. The biological data and details regarding the donation factors of all donors were analyzed, including age, gender, race, weight, the volume of blood collected, frequency of donation, and donation details such as place of donation, vital signs, and pre-donation hemoglobin level. Results: Among 35,134 total blood donors who donated within the study period, 159 cases of VVR occurred, with a prevalence of 0.45%. The occurrence rate of VVR was 4.5 cases for every 1000 blood donors. Among the vasovagal blood donors, the majority were from the female gender (72.3%), young age group (93%), Malay population (95%), a body weight of less than 55 kg (77.4%), and first-time blood donors (53.5%). The result showed a significant association between gender, body weight, the volume of blood collected, and first-time blood donors with vasovagal reactions. Conclusion: The prevalence of vasovagal reactions among the blood donors was relatively low. Even though it was low, if these events continue, they may have serious consequences for donors' welfare especially donor retention, and donor return rate. So, by identifying the potential donor who is at risk, few initial preventions can be practiced prior to the procedures, such as encouraging water intake, distraction techniques, and applying muscle tension in order to prevent VVR.